Pengaruh Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Dengan Pola Pikir Kewirausahaan Sebagai Variabel Mediasi - Reza Rizki Afiyati; Sudarno Sudarno; Leny Noviani (Universitas Negeri Surabaya, 2023)
Unemployment is one of the problems that hit almost all countries in the world. This study aims to determine the effect of entrepreneurship education, entrepreneurial mindset, and entrepreneurial intention. The study used descriptive quantitative method and involved approximately 157 university students who enrolled in entrepreneur course. The sampling technique used in this study is probability sampling with questionnaire as a data collection technique. This study used path analysis as data analysis technique. Findings indicate that: (1) there is a positive and significant influence between entrepreneurship education and entrepreneurial mindset. (2) there is a positive and significant influence between entrepreneurial mindset and entrepreneurial intention. (3) there is a positive and significant influence between entrepreneurial education and entrepreneurial mindset.